Feminism: Women, Equality and Empowerment in the Community - Rakan Radi Alhrahsheh, Khaled Khamis Nser, (Opción, 2019)
This study seeks to shed some light on the Moderate democratic feminist movement in order to recognize the approach used by feminists in the west and east to show their rights to men via a content analysis approach. As a result, women still suffering from the social gap that lies between them and men. In conclusion, it is also necessary to get rid of the male culture that is still performing visible and latent functions that lead to undermining the status of women in social life.